THE ROLE OF AGRICULTURAL BIOMASS IN THE FUTURE BIOECONOMY - R. Beluhova-Uzunova; M. Shishkova; B. Ivanova (Trakia Journal of Sciences)
The European Commission presented the 2018 Bioeconomy strategy, which developed an action plan for a resource-efficient, competitive and sustainable economy. The bioeconomy sectors are also linked to the European Green Deal, Stepping up Europe’s 2030 climate ambition Communication, Farm to Folk Strategy and other innovation strategies. In the transition to a low carbon world, biomass plays a crucial role as an alternative to fossil resources. In the EU, agriculture is the main source of biomass with 68% of the total supply. The paper analyses European Union agricultural biomass potential, supply and use. Agricultural biomass is part of the core bioeconomy sectors and its demand is increasing. However, the potential of biomass and its alternative uses are a major concern. Biomass is a renewable but limited resource and, on that basis, it is important to outline the balance and to pay attention to the relationship between the nutritional and industrial needs of biomass in terms of food and energy security. The policy framework in this regard has to be complex and well-targeted. The biomass use could lead to a number of benefits associated with resolving global issues. On the other hand, if sustainability is not taken into account, the opportunities for inclusive growth and development will not be achieved.